(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To assess the prevalence of preoperative anxiety and identify associated factors among patients scheduled for head, face, and neck surgery at Le Huu Trac National Burn Hospital. Subjects and methods: A cross-sectional descriptive study was conducted on 376 patients aged 18 and older, indicated for elective head, face, and neck surgery between January and May 2025. Preoperative anxiety was assessed using the Hospital Anxiety and Depression Scale - Anxiety (HADS-A). Data were analyzed using SPSS version 20.0, employing Chi-square tests and Odds Ratios (OR) with a 95% confidence interval. Results: The mean HADS-A score was 13.82 ± 3.26, with 69.9% of patients exhibiting clinical anxiety. The most prevalent symptoms included fear of something terrible happening (72.1%) and persistent worrying thoughts (70.5%). Regression analysis revealed that preoperative anxiety was significantly associated with: male gender (OR = 2.50), age > 45 years (OR = 2.62), rural residence (OR = 2.23), and being married (OR = 3.63). Notably, the risk of anxiety increased substantially in patients with comorbidities (OR = 15.63), declining health status upon admission (OR = 9.47), and long-term burn scar complications (OR = 6.51), with p < 0.05. Conclusion: The prevalence of preoperative anxiety among patients undergoing head, face, and neck burn surgery is remarkably high. These findings underscore the urgent need for standardized psychological assessment and specialized intervention protocols. Priority should be given to elderly patients, those with underlying medical conditions, and complex scar complications to improve the quality of comprehensive care.